Analysis of student’s learning outcomes test questions Department of Automotive Engineering FT UNP - Hendra Dani Saputra; Sartika Anori; Donny Fernandez; Dedi Setiawan (Universitas Negeri Padang, 2022)
This study is a follow-up to the results of previous studies, which stated that e-learning media did not have a significant effect on improving learning outcomes. One way of measuring learning outcomes is by presenting test questions on E-Learning media. So that a good test item will be able to provide a good measurement of learning outcomes. This research is included in quantitative descriptive research. The research aims to see the level of validity, reliability, difficulty index and Different power test questions for students of the Department of Automotive Engineering, FT UNP. The research method presenting test items in the form of multiple choice. Then proceed with quantitative analysis of the test items. The results of the analysis will provide an overview of the criteria for valid items of 84% and the reliability index of the questions in the criteria of 0.899. The results of the test difficulty index analysis, that 80% of the test questions are included in the category of good test items. As many as 20% of the test questions including the category are too easy. The results of the analysis of the different power of the test items are 28% including the bad classification. Classification test questions are sufficient at 40%. Classification of different test items is good at 32%. The category of good test items is a category of test items with sufficient and good classification.